Inter-Rater Reliability of Air/Saline HyCoSy, HyFoSy and HyFoSy Combined With Power Doppler for Screening Tubal Patency - Ludwin, Inga; Ludwin, Artur; Nastri, Carolina O.; Coelho Neto, Marcela A.; Kottner, Jan; Martins, Wellington P. (Ultraschall in der Medizin - European Journal of Ultrasound, 2019)
Purpose To estimate the inter-observer reliability and agreement of offline analyses of three different ultrasound techniques for assessing tubal patency.Methods 100 tubes (n = 100) in 50 women were evaluated for tubal patency between November 2013 and July 2015 using ultrasound as index tests and laparoscopy as the reference standard. Three different ultrasound techniques were applied: two-dimensional grayscale ultrasound using air + saline as the contrast media (2D-HyCoSy); two- and three-dimensional grayscale ultrasound using foam as the contrast media (2 D/3D-HyFoSy); and the same technique but adding bi-directional power Doppler (2 D/3D-Doppler-HyFoSy). The videos containing full standardized exams using these three techniques were split into three parts, anonymized, encoded, randomized and reassessed in Nov. 2015 by two observers who assessed tubal patency using standardized criteria. These observers were blinded to any clinical information and each other’s results. Proportions of observed agreement (po) and Cohen's Kappa (κ) including the 95 % confidence intervals (CI) were calculated.Results The inter-observer reliability/agreement in 2 D/3D-Doppler-HyFoSy (po = 0.99, κ = 0.95, 95 % CI: 0.93 – 0.97) was higher compared to 2D-air/saline-HyCoSy (po = 0.83, κ = 0.55, 95 % CI: 0.40 – 0.68) and 2 D/3D-HyFoSy (po = 0.92, κ = 0.67, 95 % CI: 0.54 – 0.76).Conclusion The inter-observer reliability and agreement of the diagnosis of tubal patency evaluating stored videos are improved when foam and power Doppler are used during acquisition. Therefore, this technique may be preferred to minimize misclassification and misdiagnosis.
Keywords: gynecology; infertility; fallopian tube patency test; reproducibility; specificity